2015
DOI: 10.1111/1365-2745.12394
|View full text |Cite
|
Sign up to set email alerts
|

How do climate and topography influence the greening of the forest‐tundra ecotone in northern Québec? A dendrochronological analysis ofBetula glandulosa

Abstract: Summary1. NDVI analysis and repeated aerial photographs have revealed significant shrub expansion in many subarctic regions. While the recent increase in temperature is usually considered to be the main driver of this phenomenon at regional scales, very little is known about the local heterogeneity of shrub responses across the landscape. 2. In this study, we aim to identify the climatic factors controlling the growth of the largely distributed shrub species Betula glandulosa in three types of environments (te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 90 publications
7
67
1
Order By: Relevance
“…However, a relative scarcity of landscape‐scale investigation has made it difficult to connect plot‐level experimentation to regional greening trends (Hobbie & Kling, ). Landscape factors like topography, disturbance, and biotic interactions may modulate rates of shrub expansion (Ackerman & Breen, ; Christie et al., ; Olofsson et al., ; Ropars, Levesque, & Boudreau, ; Schuur, Crummer, Vogel, & Mack, ). A poor understanding of the heterogeneity of shrub expansion across arctic landscapes inhibits accurate incorporation shrub feedbacks into mechanistic climate models such as dynamic global vegetation models (e.g., Sitch et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a relative scarcity of landscape‐scale investigation has made it difficult to connect plot‐level experimentation to regional greening trends (Hobbie & Kling, ). Landscape factors like topography, disturbance, and biotic interactions may modulate rates of shrub expansion (Ackerman & Breen, ; Christie et al., ; Olofsson et al., ; Ropars, Levesque, & Boudreau, ; Schuur, Crummer, Vogel, & Mack, ). A poor understanding of the heterogeneity of shrub expansion across arctic landscapes inhibits accurate incorporation shrub feedbacks into mechanistic climate models such as dynamic global vegetation models (e.g., Sitch et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Shrubs either have expanded in patch size (Sturm et al, 2001a;Tape et al, 2006;Ropars & Boudreau, 2012;Tremblay et al, 2012), recruited in areas where they were less abundant in the past (Sturm et al, 2001a;Frost et al, 2013;Frost & Epstein, 2014;B€ untgen et al, 2015) or have increased in height (Myers-Smith et al, 2011b;Paradis et al, 2016). Though this increase in tundra shrubs has been attributed to recent warming in tundra ecosystems (Elmendorf et al, 2012;Ropars et al, 2015), the climate sensitivity of shrub growth has been demonstrated to be variable across the tundra biome (Myers-Smith et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Dendrochronological approaches have successfully been applied to shrub species to analyze temporal and spatial processes in fast-changing tundra ecosystems (e.g., B€ ar et al, 2008;Forbes et al, 2010;Blok et al, 2011;Myers-Smith et al, 2015a;Ropars et al, 2015). Like trees, shrubs form annual growth rings that can be related to climate variables (e.g., Myers-Smith et al, 2015a) or disturbances in ecosystem processes such as landslides (e.g., Gers et al, 2001) and permafrost degradation (e.g., Gaertner-Roer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Warmer summers and longer growing seasons enhance shrub growth directly by increasing their photosynthetic rate (Chapin, ; Hallinger, Manthey, & Wilmking, ; Post et al., ). This is supported by dendrochronological studies on tundra shrubs that have shown a positive relationship between radial growth and summer temperature (Boudreau & Villeneuve‐Simard, ; Forbes, Fauria, & Zetterberg, ; Ropars, Lévesque, & Boudreau, ). Warmer temperatures also increase shrub growth indirectly by warming the soil, which results in increased microbial soil decomposition and greater nutrient availability for shrub growth (Loffler, Cypionka, & Loffler, ; Rustad et al., ).…”
Section: Introductionmentioning
confidence: 59%
“…The absence of a significant effect of our warming treatment on B. glandulosa radial growth should not be used to discard the importance of warmer temperatures for shrub growth. In fact, summer air temperatures and growing season degree‐days have been shown to control shrub growth both in temperature‐enhancement experimental studies (Arft et al., ; Wahren et al., ; Walker et al., ) and in dendrochronological studies (Myers‐Smith et al., ; Ropars et al., ). Our results rather suggest that either our OTCs did not increase air temperature sufficiently to influence radial growth or that they resulted in unwanted negative effects (extreme temperatures or lower air humidity).…”
Section: Discussionmentioning
confidence: 99%